Alcohol Consumption and Scholastic Performance of Collegiate Physical Education Students - Andacao, Arvin Alcaraz; Lad, Fermar Mapayo (Universitas Pendidikan Indonesia, 2021)
Alcohol is widely used in the world. Either for happiness or resolving problems, college students continue to have interaction with alcoholic drinks. This paper was aimed to examine the connection between alcohol intake and scholastic performance of second-year college students who took Physical Education subject in Davao Oriental State College of Science and Technology. The authors employed descriptive-correlational design with 115 students as samples out of 377 participated respondents. One set of adopted, contextualized, and tested 15-items of types of drinker instrument gaining excellent Cronbach’s alpha was used. Academic grades had been acquired and generated from an electronic database school system for academic records of the students. The findings discovered that the general level of alcohol consumption of the students was moderate, while the overall educational performance score was generally determined as satisfactory. The students aged 15 to 17 years gained f value 6758.46 (p0.01), while the students aged 18 to 20 years gained f=3564.71 (p0.01). Each of the result defined the sizable distinction within the alcohol consumption of college students. Meanwhile, the investigation also observed an extensive distinction in the level of alcohol use analyzed by gender (f=1780.55; p0.01). Courses and study time parameters did not show statistically significant difference in alcohol consumption. Finally, alcohol intake was not significantly correlated to instructional performance. Furthermore, the problem and high-risk of drinking in students had been found out for the maximum salience of the study. A functional and sustainable moral recovery program of each school organization that includes risk assessment, alcohol and drug education, mental health, physical exercises, games and sports, and recreational activities is recommended.